Identifying Welfare Effects from Subjective Questions - Ravallion, Martin; Lokshin, Michael (World Bank, Washington, DC, 2014)
The authors argue that the welfare inferences drawn from subjective answers to questions on qualitative surveys are clouded by concerns about the structure of measurement errors and how latent psychological factors influence observed respondent characteristics. They propose a panel data model to high-quality panel data for Russia for 1994-96, they find that some results widely reported in past studies of subjective well-being appear to be robust but others do not. Household income, for example, is a highly significant predictor of self-rated economic welfare; per capita income is a weaker predictor. Ill health and loss of a job reduce self-reported economic welfare; per capita income is a weaker predictor. Ill health and loss of a job reduce self-reported economic welfare, but demographic effects are weak at a given current income. And the effects of unemployment is not robust. Returning to work does not restore a sense of welfare unless there is an income gain. The results imply that even transient unemployment brings the feeling of a permanent welfare loss, suggesting that high unemployment benefits do not attract people out of work but do discourage a return to work.